Sacred and profane in the poetry of Nizar Qabbani - Mahdi, Yasser (Al-Adab Journal, 2023)
When addressing objectively the dialectic of the sacred and the profane in Nizar Qabbani’s poetry, it becomes clear to us the poet’s tendency to have a dialectic of the sacred and the profane in a different way to the concept of these two terms compared to the rest of the poets and the change in the concept of beauty and aesthetic between the poet Nizar Qabbani and the rest of the other poets who tried to imitate him and towards Towards him in a follower manner, but it is a crude tradition that does not reach the spirit of Nizar the poet, who is soaring in the gardens of Arabic poetry, which made him a prominent icon referred to in stigmatization because of the depth of his experience and his breaking of the familiar that other poets were not accustomed to in terms of dealing with the relationship between men and women as they are the secret of life and its continuity. Nizar Qabbani entered the world of women, a fantasy or a lived reality, while the other poets were mere followers of him in his poetic approach and behavior, and this is what made him a poetic phenomenon referred to as illusion.